BIOREGIONAL IDENTITY AND DISPLACEMENT: A STUDY OF HOME, MEMORY AND SPATIAL CONSCIOUSNESS IN 'A HOUSE FOR MR. BISWAS’ - Dewangan, Nandkumar; Khan, A.A.; Talat, Qamar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper examines V.S. Naipaul's 'A House for Mr. Biswas' through the lens of bioregionalism, focusing on the interplay between identity, displacement, and spatial consciousness. By analyzing the protagonist's quest for a home within the context of colonial Trinidad, this study explores how bioregional identity is shaped, challenged, and reimagined in the face of cultural and geographical displacement. The research employs close textual analysis and draws on theoretical frameworks from bioregional studies, postcolonial theory, and spatial theory to investigate the novel's portrayal of home, memory, and place-based identity. Findings suggest that Biswas's struggle for a house represents a broader search for bioregional belonging in a colonized space, highlighting the complex relationship between individual identity and place in postcolonial contexts. This paper contributes to the growing body of literature on bioregional approaches to postcolonial studies and offers new insights into Naipaul's seminal work.